Optimalisasi Perencanaan SDM Kesehatan di Wilayah Terpencil: Studi Kasus Dinas Kesehatan Kabupaten Tolikara, Papua - Layrvina, Nayssa Anggun Kirmantika, Kurnia Dwi Wahyu Amalia, Rauly Sijabat (PT Wahana Global Education, 2025)
This study aims to examine in depth the practice of human resource planning (HRP) in the health sector within remote regions, particularly in Tolikara Regency, Papua. The limited number and quality of health workers, coupled with the lack of integrated data-based planning systems, are the main barriers to optimizing health services. This research adopts a descriptive qualitative approach through in-depth interviews and document analysis. The results reveal that HR planning remains non-strategic, lacks support from digital HR information systems, and fails to provide training aligned with actual needs. The use of technology such as HRIS, competency-based training, and strengthened career pathing are essential to ensure the continuity of quality health services in underdeveloped, frontier, and outermost regions.